A Planar Wideband Antenna for Full Duplex Communication With Significant Peak Gain - Sandeep Rana; Amit Kumar; Akhilesh Mohan; Binod Kumar Kanaujia; Ladislau Matekovits (IEEE Access)
This paper presents a compact and planar, in-band full-duplex antenna that offers significant isolation across a broad range of frequencies. In order to attain a wide impedance bandwidth within a limited physical space, two half-resonating modes of a microstrip patch antenna (MPA), namely TM $_{0,3/2}$ and TM $_{1,1/2}$ , are stimulated in close proximity. Moreover, the utilization of a parasitic strip that acts as a $λ $ /2 resonator, assists in increasing the inter-port isolation. A prototype is fabricated and further measurements indicate that the proposed design offers inter-port isolation better than 30 dB across its wide operating band of 5.95-6.47 GHz, which corresponds to approximately 9% impedance bandwidth ( $\vert $ S $_{11}\vert $ , $\vert $ S $_{22}\vert \lt -10$ dB). Additionally, the prototype exhibited a significant peak gain of 8.2 dBi.